2019
DOI: 10.1108/bij-12-2018-0415
|View full text |Cite
|
Sign up to set email alerts
|

Lean and Green: practices, paradigms and future prospects

Abstract: Purpose The purpose of this paper is to present an overview of the conceptual framework related to the Lean and Green practices, paradigms, future prospects and problems, indicating points of convergence and divergence between them. Design/methodology/approach Based on this premise, through vast literature systematization, the authors sought to categorize studies in order to consolidate constructs, reinforcing aspects regarding the positive and negative approaches and pointing out the gaps in the current sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…After analyzing the information from publications, seven categories were elaborated based on the classification used by Ferreira et al . (2017) and Marco-Ferreira et al . (2019), by adding and adapting alternatives, thereby resulting in the following descriptions: Methodology c ategorization.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…After analyzing the information from publications, seven categories were elaborated based on the classification used by Ferreira et al . (2017) and Marco-Ferreira et al . (2019), by adding and adapting alternatives, thereby resulting in the following descriptions: Methodology c ategorization.…”
Section: Methodsmentioning
confidence: 96%
“…This type of research can aid in the identification of research constructs and scientific gaps, as well as be relevant to emerging themes and enable the identification of new research themes (Ansari and Kant, 2017; Marco-Ferreira et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The difference between lean and green waste is that the first is about non-value-added activities, and the second is about needless utilization of water, electricity and natural assets (Mollenkopf et al , 2010; Marco-Ferreira et al , 2020). Gadekar and Gadekar (2014) introduced an incorporated framework for these practices for attaining both financial and ecologically sustainable performance in an organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, there are enough pieces of evidence that showed that the implementation of integrated lean-green manufacturing system has encouraged operations managers and decision-makers to seriously consider and examine whether it can work in their manufacturing organizations and improve the quality of outcome and performance (Kushwaha and Talib, 2020;Thanki et al, 2016;Rothenberg et al, 2001;Khanam et al, 2015). For example, Marco-Ferreira et al (2019) in their review study presented an overview of the conceptual framework related to the lean-green practices, paradigms and future prospects. The results demonstrated that positive approximation of the lean-green union influences other environmental performance variables.…”
Section: Bij 282mentioning
confidence: 99%